The relationship between patient empowerment and related constructs, affective symptoms and quality of life in patients with type 2 diabetes: a systematic review and meta-analysis - Andrea Duarte-Díaz; Andrea Duarte-Díaz; Andrea Duarte-Díaz; Andrea Duarte-Díaz; Lilisbeth Perestelo-Pérez; Lilisbeth Perestelo-Pérez; Lilisbeth Perestelo-Pérez; Amado Rivero-Santana; Amado Rivero-Santana; Amado Rivero-Santana; Wenceslao Peñate; Yolanda Álvarez-Pérez; et al. (Frontiers Media S.A., 2023)
IntroductionThe aim of this systematic review is to assess the relationship between patient empowerment and other empowerment-related constructs, and affective symptoms and quality of life in patients with type 2 diabetes.MethodsA systematic review of the literature was conducted, according to the PRISMA guidelines. Studies addressing adult patients with type 2 diabetes and reporting the association between empowerment-related constructs and subjective measures of anxiety, depression and distress, as well as self-reported quality of life were included. The following electronic databases were consulted from inception to July 2022: Medline, Embase, PsycINFO, and Cochrane Library. The methodological quality of the included studies was analyzed using validated tools adapted to each study design. Meta-analyses of correlations were performed using an inverse variance restricted maximum likelihood random-effects.ResultsThe initial search yielded 2463 references and seventy-one studies were finally included. We found a weak-to-moderate inverse association between patient empowerment-related constructs and both anxiety (r = −0.22) and depression (r = −0.29). Moreover, empowerment-related constructs were moderately negatively correlated with distress (r = −0.31) and moderately positively correlated with general quality of life (r = 0.32). Small associations between empowerment-related constructs and both mental (r = 0.23) and physical quality of life (r = 0.13) were also reported.DiscussionThis evidence is mostly from cross-sectional studies. High-quality prospective studies are needed not only to better understand the role of patient empowerment but to assess causal associations. The results of the study highlight the importance of patient empowerment and other empowerment-related constructs such as self-efficacy or perceived control in diabetes care. Thus, they should be considered in the design, development and implementation of effective interventions and policies aimed at improving psychosocial outcomes in patients with type 2 diabetes.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020192429, identifier CRD42020192429.